THE IMPLEMENTATION OF PEER ASSESSMENT IN READING SKILL THROUGH TASK BASED LEARNING AT GRADE TENTH IN SMA NEGERI 1 LABUHAN DELI - Khairani; Dr. Anni Holila Pulungan, M.Hum.; Ade Aini Nuran (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
The aim of this study is to analyze the implementation of peer assessment in reading skill through task based learning at grade tenth students in SMA Negeri 1 Labuhan Deli. It used qualitative research method through four stages; 1) Data collection, 2) Data Reduction, 3) Data presentation, and 4) Conclusion and verification. The data of this research were peer assessment used by each teacher and sources of data in this research were three English teachers at grade tenth students in SMA Negeri 1 Labuhan Deli. The techniques of collecting the data were by conducting observations, interviews, and documentations. The findings showed that two teachers applied peer assessment good, and one teacher didn’t applied peer assessment. The result showed that the implementation of peer assessment in reading skill through task based learning at grade tenth in SMA Negeri 1 Labuhan Deli was almost run effectively and also categorized sufficient due to some obstacle and supporting factors.